(untitled) (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2025)
Language skills consist of speaking, reading, writing, and listening skills. This study focuses on the ability to write Javanese krama alus in the Javanese language subject at the junior high school level. This study aims to determine the level of writing skills and analysis of junior high school students using Javanese krama alus. The subjects of this study were two classes of grade VIII students of SMP Negeri 20 Semarang. The type of research is descriptive qualitative. Data collection techniques are through observation, interviews, tests, and documentation. Data analysis techniques use the Miles and Huberman analysis model. The data validity technique uses triangulation techniques. The purpose of this study is to measure students’ Javanese writing skills as an evaluation in learning Javanese to improve students’ language uploads. The results of this study show that students’ writing skills are in the sufficient category. There are errors in students’ writing at the phonology, morphology, syntax, and orthography levels. Errors at the phonology level include vowel phoneme errors of 51%, consonant phoneme errors of 31%, and consonant omissions of 18%. The morphology level includes reduplication errors of 19%, Indonesian diction errors of 39%, krama diction errors of 31%, and infixes of 11%. Next, the syntax level includes ineffective single sentences of 11%. Finally, the orthography level includes capitalization errors of 43% and punctuation errors of 45%. The implication of this research is that it can detect error patterns, teachers can identify specific areas that are difficult for students to understand, teaching is more effective and focused, this research can also provide valuable input for the preparation of textbooks.